PENGEMBANGAN MEDIA INFORMASI KARIR BERBANTUAN MULTIMEDIA INTERAKTIF ANDROID UNTUK PESERTA DIDIK SMKN 1 GODEAN - Rossydah, Soffa; Fitria, Erlin; Amalia, Ulfa; Adiningrum, Rita (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
Abstract: This research is motivated by several problems, such as students who do not fully recognize and understand the preparations that must be done in a new environment, whether in the world of courses or work. In addition, another problem is that students have difficulty determining career planning after graduating from Vocational High School because of the limited information they obtain and also the form of information provided in schools is limited.  Therefore, a career information medium is developed to increase students' insight about careers. The purpose of this research development is to produce a career information medium assisted by interactive multimedia android-based for students of SMK Negeri 1 Godean as one of the careers information media that can be used by guidance and counseling teachers in providing basic guidance and counseling services, therefore they can help students in doing career planning.  The products resulting from this research are in the form of an interactive Android multimedia-assisted career information medium with several existing features, namely career exploration features (self-exploration and environment), comprehension quizzes, information purpose features, reference features, and media developer info features. This research uses the R&D (Research and Development) method.  Based on the Borg and Gall development step model.  Based on the results of research from material expert validators, 92% of the results refer to very feasible categories, and media expert validators obtained 85% of the results with very feasible categories.  While the results of product trials in limited groups is obtained 88% that refer to very feasible categories.  The accumulated results of the feasibility assessment of material experts and media experts as well as product trial assessments limited to users is obtained results of 88%, which means it is very feasible to use in the field.   Keywords: Career Information; Career exploration; Android Interactive Multimedia.Abstrak: Penelitian ini dilatar belakangi dari beberapa masalah seperti peserta didik yang belum sepenuhnya mengerti dan memahami persiapan yang harus dilakukan pada lingkungan baru di dunia perkuliahan maupun dunia kerja. Selain itu, masalah lainnya adalah peserta didik mengalami kesulitan dalam menentukan rencana karir setalah lulus dari Sekolah Menengah Kejuruan karena keterbatasan informasi yang didapatkan oleh peserta didik dan juga bentuk informasi yang disediakan di sekolah terbatas. Maka dari itu dikembangkanlah suatu media informasi karir untuk menambah wawasan peserta didik tentang karir. Produk yang dihasilkan dari penelitian ini berupa media informasi karir berbantuan multimedia interaktif android dengan beberapa fitur yang ada, yaitu fitur eksplorasi karir (eksplorasi diri dan lingkungan), quiz pemahaman, fitur tujuan informasi, fitur refrensi dan fitur info pengembang media. Penelitian ini menggunakan metode R&D (Research and Development). Berdasarkan model langkah pengembangan Borg and Gall. Berdasarkan hasil penelitian dari validator ahli materi didapatkan hasil 92% dengan kategori sangat layak, dan validator ahli media didapatkan hasil 85%. dengan kategori sangat layak. Sedangkan hasil uji coba produk pada kelompok terbatas didapatkan hasil 88% dengan kategori sangat layak. Akumulasi hasil penilaian kelayakan ahli materi dan ahli media serta penilaian uji coba produk terbatas pada pengguna didapatkan hasil sebesar 88%. yang berarti sangat layak untuk digunakan di lapangan.Kata kunci: Informasi Karir; Eksplorasi karir; Multimedia Interaktif Android.